2006
DOI: 10.1111/j.1365-2761.2006.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of marine fish species to a megalocytivirus, turbot iridovirus, isolated from turbot, Psetta maximus (L.)

Abstract: Turbot iridovirus (TBIV), a member of the genus Megalocytivirus in the family Iridoviridae, was isolated from diseased turbot, Psetta maximus (L.), in Korea in 2003. In this study, experimental infection of turbot, Japanese flounder, Paralichthys olivaceus (Temminck & Schlegel), and rock bream, Oplegnathus fasciatus (Temminck & Schlegel), with TBIV was performed to evaluate the viral susceptibility of these fish species. After virus exposure, the mortalities of turbot reared at 22 and 25 degrees C were 60% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…2002). TBIV showed high pathogenicity in turbot compared with rock bream [ Oplegnathus fasciatus (Temminck & Schlegel 1844)] and Japanese flounder (Oh et al. 2006).…”
Section: Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…2002). TBIV showed high pathogenicity in turbot compared with rock bream [ Oplegnathus fasciatus (Temminck & Schlegel 1844)] and Japanese flounder (Oh et al. 2006).…”
Section: Taxonomymentioning
confidence: 99%
“…The rate of replication of Megalocytivirus varies with temperature. At temperatures between 20 and 25°C, members of this genus replicate well both in vivo and in vitro (Oh et al. 2006).…”
Section: Viral Propertiesmentioning
confidence: 99%
“…Kawakami and Nakajima (2002) reported that the disease caused by a megalocytivirus, termed red seabream iridovirus (RSIV), occurred in 31 cultured fish species (included within orders Perciformes, Pleuronectiformes, and Tetraodontiformes) in Japan. In a recent study, we also isolated a new megalocytivirus, turbot iridovirus (TBIV), from diseased turbot Scophthalmus maximus in Korea, indicating that megalocytiviruses have a broad host range (Kim et al, 2005;Oh et al, 2006). The viral genome of four megalocytiviruses, RSIV (Ehime-1 strain), ISKNV, rock bream iridovirus (RBIV) isolated from rock bream Oplegnathus fasciatus, and orange-spotted grouper iridovirus (OSGIV) isolated from orange-spotted grouper Epinephelus coioides have been completely sequenced (He et al, 2001;Kurita et al, 2002;Do et al, 2004;Lü et al, 2005).…”
mentioning
confidence: 97%
“…or i.m. injections of the homogenate from the organs of diseased fish or isolated viruses were used as the inocula in most reports (Chou et al, 1998;He et al, 2002;Jeong et al, 2006Jeong et al, , 2008aJun et al, 2009;Kim et al, 2012;Nakajima et al, 1997;Oh et al, 2006;Oshima et al, 1998). Thus, there is minimal information on the virus kinetics of fish after virus infection by immersion, which is known to closely approximate the natural infection conditions.…”
Section: T Ito and Othersmentioning
confidence: 99%